Efficient interfacial interaction for improving mechanical properties of polydimethylsiloxane nanocomposites filled with low content of graphene oxide nanoribbons. Issue 36 (19th April 2017) - Huang, Neng-Jian; Zang, Jing; Zhang, Guo-Dong; Guan, Li-Zhi; Li, Shi-Neng; Zhao, Li; Tang, Long-Cheng
Abstract : GONR-filled H-t-PDMS nanocomposites were fabricated by using a facile solvent-free process, and the reinforcement efficiency of GONRs at low filler content is superior to those of the other carbon nano-fillers. Abstract : In this work, hydroxyl-terminated polydimethylsiloxane (H-t-PDMS) nanocomposites reinforced by different contents of graphene oxide nanoribbons (GONRs) were prepared via a facile solvent-free process, and the mechanical properties of the H-t-PDMS/GONR nanocomposites were investigated and compared with the corresponding nanocomposites containing pristine carbon nanotubes (CNTs) or functionalized CNTs (f-CNTs). It was found that the GONRs with abundant functional groups showed good compatibility with the H-t-PDMS matrix at appropriate content: both good dispersion levels of the GONR sheets and strong GONR/matrix interfacial interactions were achieved at low filler content (≤0.5 wt%), although the GONR sheets showed obvious clusters in the matrix at relatively high content. Mechanical testing indicated that the incorporation of a low content of GONRs into the H-t-PDMS polymer resulted in significant improvements in both the tensile and tear strengths, e.g. about 158 and 284% at 0.5 wt% GONRs, respectively; and such reinforcement efficiency of the GONRs in the PDMS nanocomposites was much better than those of the corresponding CNTs or f-CNTs, even superior to those of other carbon nanofillers in previous PDMS-based nanocomposite systems. Based on the morphology and fracture surface analysis, the possible reinforcing mechanisms were discussed and clarified to understand the discrepancies in the mechanical properties of the nanocomposite systems studied.